Synthesis of Mn(II)-Loaded TixSi1-xO4 Composite Acting as a Visible-Light Driven Photocatalyst - Misriyani Misriyani; Eko Sri Kunarti; Masahide Yasuda (Indonesian Journal of Chemistry, 2015)
The synthesis and characterization of Mn-loaded TixSi1-xO4 (x= 0.4-0.8) composites and a preliminary study of an activity testing their ability to work as photocatalysts for the degradation of methylene blue (MB) have been studied. Synthesis was conducted by the sol-gel method at room temperature using tetraethyl orthosilicate, titanium tetraisopropoxide, and manganese(II) chloride as precursors followed by thermal treatment at 500 °C. The characterizations were performed by X-ray diffraction, FT-IR spectrometry, UV-Vis diffuse reflectance spectrometry and a surface area analyzer. The photocatalytic activity test of composites for degradation of MB was carried out in a closed reactor equipped with UV and visible lights. In this test, the effects of ratio of Ti/Si composites, Mn2+ ion concentration, pH, and time of irradiation on the effectiveness of photodegradation of MB were studied. The results indicated that Mn-Ti0.6Si0.4O4 composite could be synthesized through the sol-gel method followed by thermal treatment with a molar ratio of Ti/Si=60/40 and the optimum concentration of manganese was 2.5 wt%. The Mn-Ti0.6Si0.4O4 composite significantly increased the photodegradation of MB at pH 10, with a percent degradation of 84.41% for 30 min under irradiation of visible light. The percent degradation of Ti0.6Si0.4O4 was only 18.23% under irradiation of visible light.